Peri-implant stress distribution assessment of various attachment systems for implant supported overdenture prosthesis by finite element analysis – A systematic review - Bappaditya Bhattacharjee; Ritu Saneja; Ankita Singh; Pavan Kumar Dubey; Atul Bhatnagar (Journal of Oral Biology and Craniofacial Research)
Background: Various attachments like ball, bar-clip, magnetic attachments are used in implant supported overdentures. Finite Element Analysis (FEA) a newly innovated technology has been used in dental implantology to evaluate stress distribution patterns. There is little evidence available regarding the stress distribution in peri-implant region for implant supported overdentures. The purpose of the review was to generate scientific evidence on peri-implant stress distribution in FEA model with different types of attachments employed in implant supported overdentures. Materials and methods: Systematic review was conducted as per the Preferred Reporting Items for Systematic Reviews Guidelines and Meta-Analyses statement (PRISMA). A comprehensive search was undertaken by two reviewers from January 2020 to June 2020 with no year limits to published articles. Only in-vitro FEA studies were included. Following electronic databases were searched for published studies- PubMed, Web of Science. Characteristics of the studies tabulated and analysis of articles was done to compare different attachment systems. Results: Locator attachments showed better stress distribution than ball attachment system in all the studies but one. Two studies showed results in favour of ball attachment compared to bar-clip attachment system when stress was evaluated distal to the implants. No significant difference in terms of stress concentration could be generated between ball versus magnetic/equator versus locator attachment system due to less number of studies and conflicting results. Conclusion: Various studies showed different results due to heterogenicity in selected attachment systems and study designs. Locator attachments showed favourable stress distribution around peri-implant bone than other attachments.